Digital technologies and eudaimonic well-being in the emerging adults - Zambianchi, Manuela (2023)
Referring to the theoretical assumptions of Positive Technology, the study examined attitudes towards ICTs, the use of specific technologies and their relationship with eudaimonic psychological well-being (PWB) in emerging adults. 204 emerging adults (mean age 21.61, SD = 2.99; range 19-30; female 85 (49%), male 108; (56%) participated in the research. The use of specific information technologies is positively associated with the possession of attitudes favorable to them, and with different components of eudaimonic psychological well-being. The use of emails is positively linked to greater global eudaimonic well-being, a greater sense of personal growth, the presence of numerous life projects and satisfactory social relations. The use of predominantly iconic systems such as Instagram appears instead linked to a lower perceived autonomy.